Learning clinical reasoning skills during the transition from a medical graduate to a junior doctor - Karunaratne, D.; Chandratilake, M.; Marambe, K. (Centre Medical Education, 2024)
INTRODUCTION: The literature confirms the challenges of learning clinical reasoning experienced by junior doctors during their transition into the workplace. This study was conducted to explore junior doctors' experiences of clinical reasoning development and recognise the necessary adjustments required to improve the development of clinical reasoning skills. METHODS: A hermeneutic phenomenological study was conducted using multiple methods of data collection, including semistructured and narrative interviews (n=18) and post-consultation discussions (n=48). All interviews and post-consultation discussions were analysed to generate themes and identify patterns and associations to explain the dataset. RESULTS: During the transition, junior doctors’ approach to clinical reasoning changed from a ‘disease-oriented’ to a ‘practiceoriented’ approach, giving rise to the ‘Practice-oriented clinical skills development framework’ helpful in developing clinical reasoning skills. The freedom to reason within a supportive work environment, the trainees’ emotional commitment to patient care, and their early integration into the healthcare team were identified as particularly supportive. The service-oriented nature of the internship, the interrupted supervisory relationships, and early exposure to acute care settings posed challenges for learning clinical reasoning. These findings highlighted the clinical teachers' role, possible teaching strategies, and the specific changes required at the system level to develop clinical reasoning skills among junior doctors. CONCLUSION: The ‘Practice-oriented clinical skills development framework’ is a valuable reference point for clinical teachers to facilitate the development of clinical reasoning skills among junior doctors. In addition, this research has provided insights into the responsibilities of clinical teachers, teaching strategies, and the system-related changes that may be necessary to facilitate this process.
Not Indexed
Keywords: Medical graduates; Junior doctor transition; Hermeneutic phenomenology; Qualitative research; Clinical reasoning; Medical decision making